Multilingual Urban Scandinavia - Hårstad, Stian (NOA - Norsk som andrespråk, 2012)
Pia Quist & Bente A. Svendsen (red.): Multilingual Urban Scandinavia. New Linguistic Practices. Multilingual Matters 2010. 252 (+ xxiii) sider.